NILAI PERUSAHAAN: DAMPAK INTERAKSI ANTARA PROFITABILITAS DAN RISIKO FINANSIAL PADA PERUSAHAAN MANUFAKTUR - Meythi Meythi; Oktavianti Oktavianti; Riki Martusa (Jurnal Keuangan dan Perbankan, 2014)
This research was aimed to examine and find out the empirical evidence of the impact of the interaction betweenprofitability and financial risk on firm value. Samples used in this research were manufactured companieslisted in Indonesia Stock Exchange in 5 years observation period (2007-2012). The total samples were 31companies. Sample election was done by using the purposive sampling method. The result of moderatedregression analysis (MRA) showed that there was no interaction effect between profitability and financial riskon firm value. Thus, the hypothesis of the research was not empirically supported.